Increased exposure to statins in patients developing chronic muscle diseases: a 2-year retrospective study. Issue 5 (3rd September 2007) - Sailler, L; Pereira, C; Bagheri, A; Lapeyre-Mestre, M; Montastruc, J L; Arlet, P; Arlet-Suau, E; Uro-Coste, E; Roussel, H; Adoue, D; Fournie, B; Zabraniecki, L; et al.
Abstract : Objective: Case reports have suggested that lipid-lowering drugs (LLDs), especially statins, could induce or reveal chronic muscle diseases. We conducted a study to evaluate the association between chronic muscle diseases and prior exposure to LLDs. Method: This was a retrospective study of chronic primary muscle disease cases newly diagnosed at the Toulouse University Hospitals between January 2003 and December 2004 among patients living in the Midi-Pyrénées area, France. All patients remained symptomatic for more than 1 year after drug withdrawal, or required drugs for inflammatory myopathy. Data on the patient's exposure to LLDs and to other drugs were compared with that of matched controls (5/1) selected through the Midi-Pyrénées Health Insurance System database. Results: A total of 37 patients were included in the study. Of those, 21 (56.8%) suffered from dermatomyositis (DM) or polymyositis (PM), 12 (32.4%) from genetic myopathy, and 4 (10.8%) from an unclassified disease. The prevalence of exposure to statins was 40.5% in patients and 20% in controls (odds ratio (OR) 2.73, 95% confidence interval (CI) 1.21–6.14; p<0.01). There was a significant positive interaction between statins and proton pump inhibitors exposure (weighted OR 3.3, 95% CI 1.37–7.54; p = 0.02). Statin exposure rate was 47.6% among patients with DM/PM (OR 3.86, 95% CI 1.30–11.57; p<0.01). There was no difference between patients and controls for exposure to fibrates. Conclusion: Patients who developed chronic muscle diseases after the age of 50, including DM/PM, had a higher than expected frequency of prior exposure to statins. Further studies are needed to confirm this association and the role of proton pump inhibitors.